Price and Productivity Trends in Manufacturing Industries - Raines, Fredric Q. (The Review of Economics and Statistics, 1967)
G ENERAL price stability is the result of offsetting price movements in individual industries. Over large sectors of the United States economy price movements are the outcome of a complex interaction between competitive and monopolistic elements. During periods of high employment, competitive pressures on prices are weakened, and price stability where market power is present must emanate mainly from developments on the supply side. The purpose of this paper is to examine one way in which these supply-oriented developments manifest themselves the relationship between price trends and productivity trends for one sector of the economy manufacturing. The relationship between price and productivity trends in manufacturing industries is examined from two different viewpoints: (1) the Administration's price-wage guideposts, and (2) expected price movements where an industry attempts to maintain a target rate of return on capital. The first has been put forth as a theoretical norm of how prices should behave in areas where market power is present. The second has been found by many observers to be a plausible and useful explanation of price policies in such areas. To what extent has the price-productivity relationship reflected the competitive norm? To what extent has it reflected attempts to maintain target rates of return? Under what conditions are supply dominated price policies, as reflected in the target rate model, compatible with price stability? To implement the empirical investigation of these questions, estimates have been made of price and productivity trends in 26 manufacturing industries over the five-year period, 1959-1964, and in 19 manufacturing industries over the preceding five-year period, 1954-1959 (1964 was the latest year of complete data when the empirical work for this study was done). Wholesale price indexes were used, and productivity refers to output per all employee man-hours. The basic working definition adopted was that is measured by average annual (compound interest) percentage change from the initial to the terminal year of the five-year period. That this definition may have introduced some cyclical distortion is recognized, and where the facts appeared to warrant it a longer-run productivity trend was used. Choice of the particular industries was determined by availability of data, but they constitute a broad sample of the manufacturing sector, accounting for 34 per cent of manufacturing value added in the 1954-1959 period, and 41 per cent in the 1959-1964 period. Estimated price and productivity trends for all industries included in this study, together with a discussion of data sources and methods are presented in the appendix.